LANGUAGE IDENTITY OF DIALECT CARRIERS USED BY PEOPLE IN ZHURAVKA VILLAGE, SHPOLA DISTRICT, CHERKASY REGION - Щербина, Тетяна (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
Nowadays records of coherent dialectal speech became the field of research, in which the most complete reproduction of the specificity of the multifaceted speech space and the uniqueness of the creator of dialectal texts are revealed. It is important to study the speech of speakers of a separate dialect belonging to the southern zone of the Middle-Upper Dnieper dialect, the Upper-Dnipro group of dialects of the eastern zone of the Middle-Upper Dnieper-Steppe frontier. There is no comprehensive study of the linguistic identity of the dialect carrier – the representative of the mixed-transitive dialect in modern linguistics, which is due to the novelty and relevance of our research. The purpose of the proposed article is to analyze the phonetic features of the speech of the inhabitant of the dialect of Zhuravka village of Shpola district of Cherkasy region, to distinguish the typical features of the dialect system, and the individual, peculiar to the discourse of the dialect carrier. Research methods. Study of the linguistic characteristics of the native speaker of Zhuravka village of Shpola district of Cherkasy region became possible due to the observation of behavior, actions of the respondent, which enabled us to record his speech during the performance of agricultural work, work in the kitchen, rest, communication with family members, neighbors, and to accumulate complete evidence of the person himself and the specifics of his speech activity. Particularly effective was the «inclusion in the linguistic existence of the dialect carrier», or the application of the «method of coexistence», which is based on the psychological contact between the researcher and informant and the duration of the observation. In accordance with the above method, the respondent's speech was recorded in the natural conditions of a relaxed communication. Sometimes they used a poll to clarify the semantics and use of individual words, phraseologisms, and etc. Main results of the study. The least individualized in the speech of the respondent are phonetic features, which reflect the features of dialect of Zhuravka village of Shpola district of Cherkasy region. Specific features inherent in dialect transmission are non-systemic phonemes /o/ sounds [ou], [y]; sporadic implementation of a phoneme /i/ by a sound /u/ at the beginning of the words, while this feature is leveled with the other representatives of the dialect.; the transition /e/ in [a] in the suffix -en-in passive participles, as opposed to the parallel use of the suffix -an and -en in the dialect; different degree of preservation of the opposition [p]: [p'] in the declination forms of nouns to-p because of the confusion of the declination groups; realization /f/ as [f] only in proper names. Analysis of speech of dialect carrier revealed a clear distinction between speech codes, depending on the situation of communication, the interlocutor and the topic of conversation. Scientific novelty of research results. In the article for the first time the phonetic features of the speech of the carrier of dialect are presented in Zhuravka village, of Shpola district, of Cherkasy region, typical dialectal and individual features are revealed. Conclusions and specific suggestions of the author. Vocalism and consonantism of dialect of Zhuravka village, of Shpola district of Cherkasy region reveal the characteristic features of the southern zone of the Middle Upper Dnieper dialect: the preservation of the main features of the Middle-Upper-Dnieper foundation with the layers of features of the steppe dialect. Individual peculiarities of the informant's speech are expressed in the flexibility to distinguish speech situations and switch codes «literary»: «dialectal» depending on the interlocutor and conversation, preservation of dialectal features compared with the representatives of the younger age, in which they are lost. The results of the study provide the basis for further study of the specificity of the dialect of Zhuravka village, Shpola district, Cherkasy region. In particular, we consider the analysis of grammatical peculiarities of the dialect carrier speech on the material of connected texts.